Towards impact-based flood forecasting and warning in Malaysia: A case study at Kelantan river - Sidek L.M.; Basri H.; Mohammed M.H.; Marufuzzaman M.; Ishak N.A.; Ishak A.M.; Omar B.Z.C.; Osman S.; Ramly S.; Hassan M.H. (IOP Publishing Ltd, 2023)
Color; Environmental technology; Flood control; Gas engineering; Geology; Sustainable development; Technological forecasting; Water levels; Community based approach; Early Warning System; Guidance information; Institutional change; Project development; Skills development; Technological innovation; Warning informations; Floods